The Influence of Cross-Sectional Shape and Orientation of Micropillar Surface on Microdroplet Formation by a Dewetting Process - Bambang Arip Dwiyantoro; Shiu-Wu Chau (Journal of Engineering and Technological Sciences, 2013)
In this study the dewetting process on micropillars of three different cross-sectional shapes, i.e. circular, square and triangular, was numerically investigated. The influence of the orientation of the triangular and square micropillars on the dewetting behavior was also studied. The numerical simulations showed that the cross-sectional shapes of the micropillars and their orientation play an important role in determining the flow pattern of the dewetting process, especially the evolution and movement of the meniscus across the micropillar before a microdroplet is formed. The diameter of the microdroplets is mainly determined by the capillary effect, viscous drag and fluid inertia contributed by the peeling rate and the thickness of the water layer above the micropillar. The numerical results also indicate that the hydraulic diameter of the micropillars (Dp) is one of the parameters governing the size of the microdroplets formed on the top surface of the micropillars after the dewetting process, while the microdroplet diameter is almost insensitive to the cross-sectional shape and orientation of the micropillars. The dimensionless diameter of the microdroplets (d) can then be expressed as a function of a dimensionless group, i.e. the Ohnesorge number (Oh), the capillary number (Ca), the dimensionless liquid thickness (H), and the contact angle (q).